MODEL OF HYDROCARBONS TRANSPORT THROUGH THE POROUS GROUND MEDIA - Gawdzik, Andrzej; Gawdzik, Jarosław; Gawdzik, Barbara; Gawdzik, Alicja (Science-based technologies, 2014)
Dispersion model of hydrocarbons transport in porous media has been presented. Mathematical description of this process allows to estimate whether the menace of ground waters can occur as a result of hydrocarbons transport through the soil. The convection term in the mass transport equation is taken into account due to the higher velocity of propagation in vertical direction. Additionally, introduction to the balance equation the biosorption link allows to take into account microorganisms influence on impurities concentration, especially on heavy oils derived compounds. To verify the theoretical model series of the experiment in the soil filter has been carried out.